2021
DOI: 10.4025/actascibiolsci.v43i1.54966
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis optimization of isoamyl butyrate from fusel oil

Abstract: Many food, cosmetic and pharmaceutical industries have increased their interest in short-chain esters due to their flavor properties. From the industrial standpoint, enzyme reactions are the most economical strategy to reach green products with neither toxicity nor damage to human health. Isoamyl butyrate (pear flavor) was synthesized by isoamyl alcohol (a byproduct of alcohol production) and butyric acid with the use of the immobilized lipase Lipozyme TL IM and hexane as solvents. Reaction variables (temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Regarding the carboxylic (fatty) acid to alcohol molar ratio, shown in Table 2 as R, it is observed that, in most of the works reported, the synthesis of esters is favored with the increase of both reagent amounts. In some researches the increase was only in the FO amount 36,47,48,53 and in others only in carboxylic acid quantity. 14,15,43,49 In most cases, the increase in the reactants concentration tends to positively influence the reaction, shifting it to increased product formation.…”
Section: Fusel Oil (Fo)mentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding the carboxylic (fatty) acid to alcohol molar ratio, shown in Table 2 as R, it is observed that, in most of the works reported, the synthesis of esters is favored with the increase of both reagent amounts. In some researches the increase was only in the FO amount 36,47,48,53 and in others only in carboxylic acid quantity. 14,15,43,49 In most cases, the increase in the reactants concentration tends to positively influence the reaction, shifting it to increased product formation.…”
Section: Fusel Oil (Fo)mentioning
confidence: 94%
“…4.50%). 34,53 Octanoic acid, known as caprylic acid, has presented antimicrobial activity on several microorganisms, including: Escherichia coli, Salmonella enterica, Staphylococcus aureus and Listeria monocytogenes. 101 3,7,11-Trimethyl-2,6,10-dodecatrienol, a terpene known as farnesol, has shown potential as an antimicrobial agent 27 and is used in agricultural crops as mite parapheromones.…”
Section: Pesticide Formulationmentioning
confidence: 99%